HUBUNGAN PENGETAHUAN REMAJA TERHADAP KEJADIAN GIZI LEBIH PADA REMAJA DI KOTA PEKANBARU - Sara Herlina; Siti Qomariah; Wiwi Sartika; Sellia Juwita (STIKes Al-Insyirah Pekanbaru, 2022)
Adolescence is a period of transition from children to adults. Adolescents or school age are the easiest period to experience nutritional problems because this period is a transition period from childhood to adulthood, especially in adolescent girls, the factor of eating frequency, irregular meal times, and the many types of food consumed lead to nutritional disorders in adolescent girls. . The purpose of this study was to determine the relationship between adolescent knowledge about overnutrition and the incidence of overnutrition in adolescents in Pekanbaru City. This study uses an analytical survey with a cross-sectional approach, the research was conducted online using google forms in Pekanbaru City. The sample in this study were teenagers who were in the city of Pekanbaru with a random sampling technique sampling the number of samples as many as 335 people. The results of the univariate analysis showed that 181 people (54%) had good knowledge and as many as 154 people (46%) lacked knowledge, and the results of the bivariate test showed that there was a relationship between adolescent knowledge about overweight and obesity with a P value of 0.000. From the results of the study, it was concluded that adolescent knowledge about nutrition had a greater influence on the incidence of overnutrition in adolescents in Pekanbaru City. It is hoped that to reduce the incidence of overnutrition, adolescents can increase knowledge about nutrition which can be obtained from various sources of information